2019
DOI: 10.3126/jpahs.v6i2.27227
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological profile of colorectal cancer managed at a university teaching hospital, Nepal

Abstract: Introductions: Colorectal carcinoma is the third most common cancer worldwide. The incidence is increasing in developing countries including Nepal. The aim of this study is to find out the clinicopathological pattern of colorectal carcinoma locally. Methods: Data were recorded retrospectively by reviewing the charts of the patients who were diagnosed and treated for in patients having colorectal cancer managed during three years period of 2016-9 at Patan Hospital, the university teaching hospital of Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 19 publications
3
8
0
Order By: Relevance
“…For left-sided CRC, common histologic subtypes were moderately differentiated, mucinous, and well-differentiated. This finding was similar to another Nepalese data of patients across all ages, where moderately differentiated (70%) was the most common histology, followed by mucinous (20%) 12 whereas, in another study of childhood and adolescence patients, mucinous (62%) was most common histology. 7,16 The various subtypes within the histology group were compared as per the tumor location however the difference was not significant.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…For left-sided CRC, common histologic subtypes were moderately differentiated, mucinous, and well-differentiated. This finding was similar to another Nepalese data of patients across all ages, where moderately differentiated (70%) was the most common histology, followed by mucinous (20%) 12 whereas, in another study of childhood and adolescence patients, mucinous (62%) was most common histology. 7,16 The various subtypes within the histology group were compared as per the tumor location however the difference was not significant.…”
Section: Discussionsupporting
confidence: 89%
“…10 In a study done across all ages in one of the teaching hospitals of Nepal, pain abdomen (86%) and bleeding per rectum (55%) were common symptoms at presentation. 12 Our study showed more left-sided tumors compared to right-sided. The left-sided tumor was more common in metastatic CRC in a study with a large sample size 9 while in a large data of patients across all ages, 67.03% of patients had right-sided CRC while 32.96% patients had left-sided CRC.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…The mean age of presentation was 54.7 years in a multicenter study comprising of 1525 patients at Colombia 7 . In a similar study by Paudyal et al 8 in Nepal and Kumar et al 9 in Oman, the mean age was 56.9 and 56 years respectively with male predominance.…”
Section: Discussionmentioning
confidence: 61%
“…In the current study, 4.8% patients were aged below 40 years of age. In a previous study in Nepal by Paudyal et al 8 , the incidence of colorectal cancer in young below 40 years of age was even higher (16.7%). Colorectal carcinomas were detected at even lower ages (less than 35 years) among 19.25% patients by Bhat et al 6 Bohorquez et al 7 had also reported 26.5% of cases diagnosed with CRC before the age of 50 years.…”
Section: Discussionmentioning
confidence: 76%